An Acuity Tool for Heart Failure Case Management: Quantifying Workload, Service Utilization, and Disease Severity. Issue 3 (May 2018) - Kilgore, Matthew D.
Abstract : Purpose: The cardiology service line director at a health maintenance organization (HMO) in Washington State required a valid, reliable, and practical means for measuring workloads and other productivity factors for six heart failure (HF) registered nurse case managers located across three geographical regions. The Kilgore Heart Failure Case Management (KHFCM) Acuity Tool © was systematically designed, developed, and validated to measure workload as a dependent function of the number of heart failure case management (HFCM) services rendered and the duration of times spent on various care duties. Primary Practice Setting: Research and development occurred at various HMO-affiliated internal medicine and cardiology offices throughout Western Washington. The concepts, methods, and principles used to develop the KHFCM Acuity Tool © are applicable for any type of health care professional aiming to quantify workload using a high-quality objective tool. The content matter, scaling, and language on the KHFCM Acuity Tool © are specific to HFCM settings. Methodology and Sample: The content matter and numeric scales for the KHFCM Acuity Tool © were developed and validated using a mixed-method participant action research method applied to a group of six outpatient HF case managers and their respective caseloads. The participant action research method was selected, because the application of this method requires research participants to become directly involved in the diagnosis of research problems, the planning and execution of actions taken to address those problems, and the implementation of progressive strategies throughout the course of the study, as necessary, to produce the most credible and practical practice improvements (I. Chein, S. W. Cook, & J. Harding, 1948 ;J. Collier, 1945 ;K. Lewin, 1946 ;H. J. Streubert & D. R. Carpenter, 1999 ). Heart failure case managers served clients with New York Heart Association Functional Class III–IV HF (American Heart Association, 2017 ), and encounters were conducted primarily by telephone or in-office consultation. Results: A mix of qualitative and quantitative results demonstrated a variety of quality improvement outcomes achieved by the design and practice application of the KHFCM Acuity Tool © . Quality improvement outcomes included a more valid reflection of encounter times and demonstration of the KHFCM Acuity Tool © as a reliable, practical, credible, and satisfying tool for reflecting HF case manager workloads and HF disease severity. Implications: The KHFCM Acuity Tool © defines workload simply as a function of the number of HFCM services performed and the duration of time spent on a client encounter. The design of the tool facilitates the measure of workload, service utilization, and HF disease characteristics, independently from the overall measure of acuity, so that differences in individual case manager practice, as well as client characteristics within sites, across sites, and potentially throughout annual seasons, can be demonstrated. Data produced from long-term applications of the KHFCM Acuity Tool ©, across all regions, could serve as a driver for establishing systemwide HFCM productivity benchmarks or standards of practice for HF case managers. Data produced from localized applications could serve as a reference for coordinating staffing resources or developing HFCM productivity benchmarks within individual regions or sites. Abstract : Supplemental Digital Content is Available in the Text.